Copper coordination cationic cellulose nanofibril solid electrolyte and preparation method and application thereof
By using copper-coordinated cationic cellulose nanofibers to prepare solid electrolytes, the problem of the energy density of lithium-ion batteries is close to the limit and the performance of polymer solid electrolytes is insufficient, and a high-performance and environmentally friendly solid electrolyte is achieved.
Patent Information
- Application Number
- CN202411583087.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The liquid electrolytes of existing lithium-ion batteries have problems such as near the limit of energy density and are flammable and easy to leak, while polymer solid electrolytes such as PEO have defects such as low room temperature ion conductivity and poor mechanical properties, which are difficult to directly apply in actual production.
Copper-coordinated cationic cellulose nanofiber filaments were used as raw materials for solid electrolytes, and solid electrolytes with excellent mechanical and electrochemical properties were prepared through etherification treatment and Cu2+ coordination reaction.
It improves the room temperature ionic conductivity and electrochemical stability window of lithium-ion batteries, improves mechanical properties, and the raw materials are renewable and naturally degradable, in line with the concept of green production.
Smart Images

Figure CN119601759A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and particularly relates to a copper coordinated cationic cellulose nanofibril solid electrolyte and a preparation method and application thereof. Background Art
[0002] Among various electrochemical energy storage devices, lithium-ion batteries have the advantages of low self-discharge rate, large charge and discharge rate, high energy density and long cycle life. They are still the ideal power source for electric vehicles, hybrid vehicles, portable electronic products and even large-scale energy storage systems.
[0003] The electrolyte used in common lithium-ion batteries is an organic solvent-based liquid electrolyte, which is usually composed of an organic solvent, a lithium salt, and an additive. Although this type of electrolyte has the advantages of high ionic conductivity and good interface wettability, the energy density of commercial liquid lithium-ion batteries (about 260W·h·kg -1 ) is close to the theoretical limit and is difficult to improve further; at the same time, organic solvents are easy to leak and burn, making the battery prone to combustion or explosion during overcharging or short circuiting, endangering the personal and property safety of users.
[0004] Polymer solid electrolytes have the characteristics of no organic solvents and can inhibit the growth of lithium dendrites, which can improve the safety performance of lithium-ion batteries. The most commonly used polymer solid electrolyte raw material is polyethylene oxide (PEO), which binds to Li through ether bonds in the amorphous region. + Binding / dissociation complete Li + However, PEO solid electrolytes have defects such as low ionic conductivity, poor mechanical properties, and high glass transition temperature due to high crystallinity at room temperature. They are also not naturally degradable and non-renewable, which is contrary to the green production concept of sustainable development and is difficult to be directly applied in actual production.
[0005] Therefore, it is necessary to select an environmentally friendly material that has excellent performance and green environmental protection properties to prepare solid electrolytes. Summary of the invention
[0006] The primary purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a method for preparing a copper coordinated cationic cellulose nanofibril solid electrolyte.
[0007] Another object of the present invention is to provide a copper coordinated cationic cellulose nanofibril solid electrolyte prepared by the method.
[0008] Another object of the present invention is to provide an application of the copper coordinated cationic cellulose nanofibril solid electrolyte.
[0009] The purpose of the present invention is achieved through the following technical solutions:
[0010] A method for preparing a copper-coordinated cationic cellulose nanofibril solid electrolyte comprises the following steps:
[0011] (1) cellulose nanofibrils (CNF) are stirred and dissolved in a NaOH / urea aqueous solution, and then glycidyl trimethylammonium chloride is added as an etherifying agent to introduce cationic groups into the cellulose nanofibrils, which are then precipitated using ethanol to obtain cationic cellulose nanofibrils;
[0012] (2) The cationic cellulose nanofibrils obtained in step (1) are immersed in a saturated Cu 2+ NaOH solution to make it react with Cu 2+ Coordination occurs to obtain a copper-coordinated cationic cellulose nanofiber suspension;
[0013] (3) centrifuging the copper-coordinated cationic cellulose nanofibril suspension obtained in step (2), using anhydrous acetonitrile as a new dispersion medium for the copper-coordinated cationic cellulose nanofibrils, and obtaining a copper-coordinated cationic cellulose nanofibril-anhydrous acetonitrile system;
[0014] (4) adding lithium salt to the copper coordinated cationic cellulose nanofibril-anhydrous acetonitrile system obtained in step (3), stirring and mixing evenly, and then casting into a mold and drying to obtain the copper coordinated cationic cellulose nanofibril solid electrolyte.
[0015] The method for preparing the copper coordinated cationic cellulose nanofibril solid electrolyte specifically comprises the following steps:
[0016] S1. Add cellulose nanofibrils (CNF) to a NaOH / urea aqueous solution precooled to -4°C to 0°C, stir and mix, and then freeze the solution in a refrigerator at -10 to -4°C, then take it out and stir at room temperature until the solution thaws to form a transparent solution; add a glycidyl trimethylammonium chloride aqueous solution (as an etherifying agent) to the transparent solution, and react under stirring conditions at 30°C to 50°C. After the reaction is completed, add glacial acetic acid to terminate the reaction, and then add anhydrous ethanol (excessive) to completely precipitate the product, take the precipitate and wash it to obtain cationic cellulose nanofibrils;
[0017] S2, placing the copper wire in a NaOH solution, and then adding the cationic cellulose nanofibrils obtained in step S1, soaking and stirring to make them mix with the Cu in the solution. 2+ The coordination reaction takes place, and after the reaction is completed, the suspension is washed with water to obtain a copper coordinated cationic cellulose nanofiber suspension;
[0018] S3, pouring the copper coordinated cationic cellulose nanofibril suspension obtained in step S2 into a centrifuge tube, centrifuging, and discarding the supernatant; then adding anhydrous acetonitrile, centrifuging again, discarding the supernatant, and repeating the operation of adding anhydrous acetonitrile for more than three times until the water is completely replaced by anhydrous acetonitrile, thereby obtaining a copper coordinated cationic cellulose nanofibril-anhydrous acetonitrile system;
[0019] S4, adding lithium salt to the copper coordinated cationic cellulose nanofibril-anhydrous acetonitrile system obtained in step S3, stirring and mixing evenly, casting into a mold, and drying to obtain the copper coordinated cationic cellulose nanofibril solid electrolyte.
[0020] The amount of cellulose nanofibrils (CNF) used in step S1 is calculated based on 3-5 g of dry cellulose nanofibrils per 100 mL of NaOH / urea aqueous solution; preferably, it is calculated based on 4 g of dry cellulose nanofibrils per 100 mL of NaOH / urea aqueous solution.
[0021] In step S1, the precooling temperature is preferably 0°C.
[0022] The concentration of NaOH in the NaOH / urea aqueous solution in step S1 is 6-7% by mass (preferably 7% by mass), and the concentration of urea is 10-14% by mass (preferably 12% by mass).
[0023] The stirring and mixing time in step S1 is 5 to 15 minutes, preferably 10 minutes.
[0024] The freezing temperature in step S1 is preferably -4°C.
[0025] The freezing time in step S1 is 3 to 5 hours, preferably 4 hours.
[0026] The concentration of the glycidyltrimethylammonium chloride aqueous solution in step S1 is 15-25% by mass, preferably 20% by mass.
[0027] The mass ratio of cellulose nanofibrils (CNF) to glycidyl trimethylammonium chloride in step S1 is 1:3 to 5, preferably 1:4.
[0028] The temperature of the stirring reaction in step S1 is preferably 40°C.
[0029] In step S1, the reaction time under stirring is 1 to 3 hours, preferably 2 hours.
[0030] The amount of glacial acetic acid described in step S1 is added according to actual needs to terminate the reaction; preferably, it is added to the system at a molar ratio of the total molar amount of NaOH and urea to the glacial acetic acid of 1:1.5-2.5; more preferably, it is added to the system at a molar ratio of the total molar amount of NaOH and urea to the glacial acetic acid of 1:1.53-1.55.
[0031] The washing in step S1 is performed using deionized water; preferably, the deionized water is used for washing more than 3 times until no other liquid remains.
[0032] The concentration of the NaOH solution in step S2 is 8-12% by mass, preferably 10% by mass.
[0033] The amount of the NaOH solution in step S2 is calculated based on 30-50 mL of NaOH solution per gram of copper wire; preferably, it is calculated based on 40 mL of NaOH solution per gram of copper wire.
[0034] The soaking time in step S2 is 3 to 7 days, preferably 3 days.
[0035] The water washing in step S2 is washing with deionized water for more than 3 times until no alkali solution remains.
[0036] The centrifugal conditions described in step S3 are: centrifugation at 10,000 rpm for 5 to 8 minutes.
[0037] The lithium salt described in step S4 is preferably LiClO4.
[0038] The mass ratio of the lithium salt in step S4 to the copper coordinated cationic cellulose nanofibrils in the copper coordinated cationic cellulose nanofibrils-anhydrous acetonitrile system is 1:4-8, preferably 1:6.
[0039] In step S4, the lithium salt can be first dissolved in anhydrous acetonitrile to form a lithium salt solution, which is then added to the copper-coordinated cationic cellulose nanofibrils-anhydrous acetonitrile system.
[0040] The mold described in step S4 is preferably a polytetrafluoroethylene mold.
[0041] The drying in step S4 is vacuum drying, preferably: vacuum drying at 50-60° C. for 24 h; more preferably: vacuum drying at 50° C. for 24 h.
[0042] A copper coordinated cationic cellulose nanofibril solid electrolyte is prepared by any of the methods described above.
[0043] The application of the copper coordinated cationic cellulose nanofibril solid electrolyte in the preparation of energy storage materials.
[0044] The copper coordinated cationic cellulose nanofibril solid electrolyte is used in the preparation of lithium metal solid-state batteries (solid-state lithium batteries, all-solid-state batteries).
[0045] The copper coordinated cationic cellulose nanofibril solid electrolyte is used in electric vehicles (electric bicycles, electric cars, etc.), energy storage devices, and portable devices (laptop computers, smart phones, etc.).
[0046] Compared with the prior art, the present invention has the following advantages and effects:
[0047] (1) The present invention provides a copper-coordinated cationic cellulose nanofibril solid electrolyte, which is mainly composed of copper-coordinated cationic cellulose nanofibrils and lithium perchlorate (LiClO4). The solid electrolyte has excellent mechanical and electrochemical properties and can effectively inhibit the growth of lithium dendrites. At the same time, the raw materials meet the requirements of being green, environmentally friendly, and naturally degradable.
[0048] (2) The copper-coordinated cationic cellulose nanofibrils of the present invention are firstly prepared by homogeneously etherifying cellulose nanofibrils with glycidyl trimethyl ammonium chloride (GTMAC) to obtain cationic cellulose nanofibrils, and then using Cu 2+ The copper-coordinated cationic cellulose nanofibrils were obtained by soaking in saturated NaOH solution.
[0049] (3) The copper-coordinated cationic cellulose nanofibril solid electrolyte prepared by the present invention improves the defects of common polymer solid electrolytes such as low room temperature ionic conductivity and poor mechanical properties. Although ordinary cellulose nanofibrils can provide the high mechanical strength required for solid electrolytes, they often form densely arranged molecular chains due to their abundant hydroxyl groups and a large number of hydrogen bonds, thereby hindering the Li + The cationic functional groups grafted on the surface of copper-coordinated cationic cellulose nanofibrils and Cu 2+ The coordination occupies more surface hydroxyl groups, reduces the number of hydrogen bonds, and helps the dissociation and transportation of lithium ions, thereby improving the Li + The room temperature ionic conductivity of the solid electrolyte can reach 7.29×10 -5 S / cm, and the electrochemical stability window can reach 4.58V.
[0050] (4) The present invention uses cellulose nanofibrils to completely replace PEO as the raw material for preparing solid electrolytes, which has the advantages of being renewable and naturally degradable, and is in line with the green production concept of sustainable development.
[0051] (5) Common polymer solid electrolytes have low room temperature conductivity, so the battery operating temperature needs to be increased. The copper-coordinated cationic cellulose nanofibril solid electrolyte prepared in the present invention has a wider thermal stability than ordinary PEO-based solid electrolytes. It still maintains structural stability at 150°C without electrolyte melting, thereby increasing the actual operating temperature range of lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 The AC impedance diagrams of the solid electrolytes prepared in Example 1 and Comparative Example 1.
[0053] Figure 2 Electrochemical stability window diagram of lithium sheet / solid electrolyte / steel sheet button cells assembled with solid electrolytes prepared in Example 1 and Comparative Example 1.
[0054] Figure 3 This is a test result diagram of the cyclic charge and discharge (charge and discharge rate is 0.5C) of a full battery assembled using the solid electrolyte prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0055] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. The test methods for which specific experimental conditions are not specified in the following examples are usually in accordance with conventional experimental conditions. Unless otherwise specified, the reagents and raw materials used in the present invention can be obtained commercially.
[0056] The materials involved in the following embodiments and comparative examples of the present invention are as follows:
[0057] The cellulose nanofibrils CNF (suspension) used were purchased from Zhejiang Jinjiahao Green Nanomaterials Co., Ltd., and the preparation method was high-pressure homogenization method, with a solid content of 2 wt%;
[0058] The sodium hydroxide (≥97%), urea (≥99.5%), glycidyltrimethylammonium chloride (≥95%) and anhydrous ethanol (≥99.5%) used were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0059] The copper wire used was cut from copper sheets (≥99.5%) purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with a diameter of 1 mm;
[0060] The lithium perchlorate (≥95.0%) used was purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.
[0061] The molecular weight of the polyethylene oxide (PEO) used is V=600000, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0062] Example 1
[0063] (1) NaOH and urea were added to deionized water to prepare a 7 wt% NaOH / 12 wt% urea aqueous solution (i.e., the mass concentration of NaOH in the NaOH / urea aqueous solution was 7%, and the mass concentration of urea was 12%), and the solution was precooled to 0°C, and then 4 g of cellulose nanofibrils CNF with an absolute dry mass was weighed and added to 100 mL of the above solution, stirred at room temperature for 10 min, placed in a -4°C refrigerator and frozen for 4 h, and then intermittently stirred at room temperature again until the solution thawed to obtain a transparent solution.
[0064] (2) Add 16 g of glycidyl trimethylammonium chloride powder to 64 mL of deionized water, stir until completely dissolved, then pour into the NaOH / urea aqueous solution containing CNF prepared in step (1), and place in a constant temperature heated magnetic stirrer at 40°C. After 2 h, add 35 g of glacial acetic acid to terminate the reaction, use anhydrous ethanol to completely precipitate cellulose, and then wash with deionized water three times to obtain cationic cellulose nanofibers.
[0065] (3) Prepare 200 mL of 10% NaOH aqueous solution (solvent is deionized water), add 5 g of copper wire thereto. Then add the cationic cellulose nanofibrils prepared in step (2) thereto, place in a magnetic stirrer for stirring and soak for 3 days. After the reaction is completed, wash with deionized water 3 times to obtain a copper-coordinated cationic cellulose nanofibril suspension.
[0066] (4) Pour the copper-coordinated cationic cellulose nanofibril suspension prepared in step (3) into a centrifuge tube and place it in a centrifuge, set the speed to 10000 rpm and the centrifugation time to 5 min. Start the machine for centrifugation. After the centrifugation is completed, pour out the supernatant in the centrifuge tube, and pour anhydrous acetonitrile of the same mass as the poured supernatant into the lower system, and centrifuge again. Repeat the above operation three times until the deionized water is completely replaced by anhydrous acetonitrile, and measure the solid content of the copper-coordinated cationic cellulose nanofibril-anhydrous acetonitrile system.
[0067] (5) Weigh 0.68 g of LiClO4 powder, add it to the copper coordinated cationic cellulose nanofibril-anhydrous acetonitrile system obtained in step (4) (the absolute dry mass of the copper coordinated cationic cellulose nanofibril in the system is 4 g), stir evenly and pour it into a polytetrafluoroethylene mold, place it in a vacuum drying oven at 50°C and vacuum dry it for 24 hours to obtain a copper coordinated cationic cellulose nanofibril solid electrolyte.
[0068] Example 2
[0069] The only difference from Example 1 is that the mass of the glycidyl trimethyl ammonium chloride powder in step (2) is adjusted to 12 g, and the other step parameters and conditions are the same as those in Example 1.
[0070] Example 3
[0071] The only difference from Example 1 is that the mass of the glycidyl trimethyl ammonium chloride powder in step (2) is adjusted to 20 g, and the other step parameters and conditions are the same as those in Example 1.
[0072] Example 4
[0073] The only difference from Example 1 is that the immersion time of the cationic cellulose nanofibrils in the solution in step (3) is adjusted to 5 days, and the other step parameters and conditions are the same as those in Example 1.
[0074] Example 5
[0075] The only difference from Example 1 is that the soaking time of the cationic cellulose nanofibrils in the solution in step (3) is adjusted to 7 days, and the other step parameters and conditions are the same as those in Example 1.
[0076] Example 6
[0077] The only difference from Example 1 is that the mass of LiClO4 powder in step (5) is adjusted to 0.5 g, and the other step parameters and conditions are the same as those in Example 1.
[0078] Example 7
[0079] The only difference from Example 1 is that the mass of LiClO4 powder in step (5) is adjusted to 1.0 g, and the other step parameters and conditions are the same as those in Example 1.
[0080] Comparative Example 1
[0081] (1) Prepare PEO and LiClO4 with a molar ratio of EO:Li of 16:1, specifically: weigh 2.82g PEO and 0.43g LiClO4, add them to 30mL anhydrous acetonitrile solvent, place in a constant temperature heated magnetic stirrer at 40°C and stir for 12h until the mixture is uniformly mixed. Then pour the obtained mixed solution into a polytetrafluoroethylene mold, place in a vacuum drying oven at 50°C and vacuum dry for 24h to obtain a PEO polymer solid electrolyte.
[0082] Comparative Example 2
[0083] (1) NaOH and urea were added to deionized water to prepare a 7 wt% NaOH / 12 wt% urea aqueous solution (i.e., the mass concentration of NaOH in the NaOH / urea aqueous solution was 7%, and the mass concentration of urea was 12%), and the solution was precooled to 0°C, and then 4 g of cellulose nanofibrils CNF with an absolute dry mass was weighed and added to 100 mL of the above solution, stirred at room temperature for 10 min, placed in a -4°C refrigerator and frozen for 4 h, and then intermittently stirred at room temperature again until the solution thawed to obtain a transparent solution.
[0084] (2) Add 16 g of glycidyl trimethylammonium chloride powder to 64 mL of deionized water, stir until completely dissolved, then pour into the NaOH / urea aqueous solution containing CNF prepared in step (1), and place in a constant temperature heated magnetic stirrer at 40°C. After 2 h, add 35 g of glacial acetic acid to terminate the reaction, use anhydrous ethanol to completely precipitate cellulose, and then wash with deionized water three times to obtain a cationic cellulose nanofiber suspension.
[0085] (3) Pour the cationic cellulose nanofibril suspension prepared in step (2) into a centrifuge tube and place it in a centrifuge, set the speed to 10000 rpm and the centrifugation time to 5 min. Start the machine for centrifugation. After the centrifugation is completed, pour out the supernatant in the centrifuge tube, and pour anhydrous acetonitrile of the same mass as the poured supernatant into the lower system, and centrifuge again. Repeat three times until the deionized water is completely replaced by anhydrous acetonitrile. Measure the solid content of the cationic cellulose nanofibril-anhydrous acetonitrile system.
[0086] (4) Weigh 0.68 g of LiClO4 powder, add it to the cationic cellulose nanofibril-anhydrous acetonitrile system obtained in step (3) (the absolute dry mass of the cationic cellulose nanofibrils in the system is 4 g), stir evenly and pour it into a polytetrafluoroethylene mold, place it in a vacuum drying oven at 50°C and vacuum dry it for 24 hours to obtain a cationic cellulose nanofibril solid electrolyte.
[0087] Comparative Example 3
[0088] (1) Prepare 200 mL of 10% NaOH aqueous solution, add 5 g of copper wire, then add 4 g of cellulose nanofibrils, place in a magnetic stirrer for stirring and soak for 3 days. After the reaction is completed, wash with deionized water 3 times to obtain a copper-coordinated cellulose nanofibril suspension.
[0089] (2) Pour the copper-coordinated cellulose nanofibril suspension prepared in step (1) into a centrifuge tube and place it in a centrifuge, set the speed to 10000 rpm and the centrifugation time to 5 min. Start the machine for centrifugation. After the end, pour out the supernatant in the centrifuge tube, and pour anhydrous acetonitrile of the same mass as the poured supernatant into the lower system, and centrifuge again. Repeat the above operation three times until the deionized water is completely replaced by anhydrous acetonitrile. Measure the solid content of the copper-coordinated cationic cellulose nanofibril-anhydrous acetonitrile system.
[0090] (3) Weigh 0.68 g of LiClO4 powder, add it to the copper-coordinated cellulose nanofibril-anhydrous acetonitrile system (the absolute dry mass of the cationic cellulose nanofibrils in the system is 4 g) obtained in step (2), stir evenly and pour it into a polytetrafluoroethylene mold, place it in a vacuum drying oven at 50°C and vacuum dry it for 24 hours to obtain a copper-coordinated cationic cellulose nanofibril solid electrolyte.
[0091] Effect Example
[0092] 1. The solid electrolytes prepared in the above Examples 1 to 7 and Comparative Examples 1 to 3 were punched into 16 mm diameter discs, and assembled into steel sheet / solid electrolyte / steel sheet button cells (button cell shell model is CR2032, the steel sheet used has a diameter of 16 mm, and the thickness is 0.5 mm and 1 mm) in a glove box to test their ionic conductivity (test temperature 30°C, 60°C). The test frequency is 0.1 MHz to 0.1 Hz. The experiment was repeated three times.
[0093] 2. The solid electrolytes prepared in the above Examples 1 to 7 and Comparative Examples 1 to 3 were punched into 16 mm diameter discs and assembled into lithium sheet / solid electrolyte / steel sheet button cells in a glove box (the button cell shell model is CR2032, the lithium sheet used has a diameter of 16 mm and a thickness of 0.5 mm; the steel sheet used has a diameter of 16 mm and a thickness of 1 mm) to test its electrochemical stability window. The test potential voltage is 2.0 V to 7.0 V, and the scan rate is set to 10 mV / s. The experiment is repeated three times.
[0094] 3. The solid electrolytes prepared in the above Examples 1 to 7 and Comparative Examples 1 to 3 were punched into 16 mm diameter discs and assembled into lithium sheet / solid electrolyte / lithium iron phosphate positive electrode button cells in a glove box (button cell shell model is CR2032, lithium sheet diameter is 16 mm, thickness is 0.5 mm; positive electrode sheet diameter is 12 mm) and the cycle performance was tested using a battery cycle system. The test voltage range is 2.0 V to 4.2 V, and the charge and discharge rate is 0.5 C. The experiment was repeated three times.
[0095] The test results of Examples 1 to 7 and Comparative Examples 1 to 3 are shown in Tables 1 and 2. The AC impedance diagrams of the solid electrolytes prepared in Example 1 and Comparative Example 1 at 30°C are shown in Tables 1 and 2. Figure 1 As shown in the figure, the electrochemical stability window of the assembled lithium sheet / solid electrolyte / steel sheet button battery is as follows Figure 2 As shown in the figure, the test results of the cycle charge and discharge (charge and discharge rate is 0.5C) of the assembled lithium sheet / solid electrolyte / lithium iron phosphate positive electrode button battery are as follows Figure 3 shown.
[0096] Table 1 Solid electrolyte performance test results of Examples 1 to 7
[0097]
[0098] Table 2 Comparative Examples 1 to 3 Solid Electrolyte Performance Test Results
[0099]
[0100]
[0101] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a copper-coordinated cationic cellulose nanofibril solid electrolyte, characterized in that: The steps include: (1) stirring and dissolving cellulose nanofibrils in a NaOH / urea aqueous solution, then adding glycidyl trimethyl ammonium chloride as an etherifying agent, introducing cationic groups into the cellulose nanofibrils, and then using ethanol to precipitate them to obtain cationic cellulose nanofibrils; (2) The cationic cellulose nanofibrils obtained in step (1) are immersed in a saturated Cu 2+ NaOH solution to make it react with Cu 2+ Coordination occurs to obtain a copper-coordinated cationic cellulose nanofiber suspension; (3) centrifuging the copper-coordinated cationic cellulose nanofibril suspension obtained in step (2), using anhydrous acetonitrile as a new dispersion medium for the copper-coordinated cationic cellulose nanofibrils, and obtaining a copper-coordinated cationic cellulose nanofibril-anhydrous acetonitrile system; (4) adding lithium salt to the copper coordinated cationic cellulose nanofibril-anhydrous acetonitrile system obtained in step (3), stirring and mixing evenly, casting into a mold, and drying to obtain the copper coordinated cationic cellulose nanofibril solid electrolyte.
2. The method according to claim 1, characterized in that The specific steps include: S1. Add cellulose nanofibrils to a NaOH / urea aqueous solution precooled to -4°C to 0°C, stir and mix, and then freeze the solution in a refrigerator at -10 to -4°C, then take it out and stir at room temperature until the solution thaws to form a transparent solution; add a glycidyl trimethylammonium chloride aqueous solution to the transparent solution, and react under stirring conditions at 30°C to 50°C. After the reaction is completed, add glacial acetic acid to terminate the reaction, and then add anhydrous ethanol to completely precipitate the product, and wash the precipitate to obtain cationic cellulose nanofibrils; S2, placing the copper wire in a NaOH solution, and then adding the cationic cellulose nanofibrils obtained in step S1, soaking and stirring to make them mix with the Cu in the solution. 2+ The coordination reaction takes place, and after the reaction is completed, the suspension is washed with water to obtain a copper coordinated cationic cellulose nanofiber suspension; S3, pouring the copper coordinated cationic cellulose nanofibril suspension obtained in step S2 into a centrifuge tube, centrifuging, and discarding the supernatant; then adding anhydrous acetonitrile, centrifuging again, discarding the supernatant, and repeating the operation of adding anhydrous acetonitrile for more than three times until the water is completely replaced by anhydrous acetonitrile, thereby obtaining a copper coordinated cationic cellulose nanofibril-anhydrous acetonitrile system; S4, adding lithium salt to the copper coordinated cationic cellulose nanofibril-anhydrous acetonitrile system obtained in step S3, stirring and mixing evenly, casting into a mold, and drying to obtain the copper coordinated cationic cellulose nanofibril solid electrolyte.
3. The method according to claim 2, characterized in that: The concentration of NaOH in the NaOH / urea aqueous solution in step S1 is 6-7% by mass, and the concentration of urea is 10-14% by mass; The concentration of the glycidyl trimethyl ammonium chloride aqueous solution in step S1 is 15-25% by mass; The mass ratio of the cellulose nanofibrils to glycidyl trimethylammonium chloride in step S1 is 1:3-5; The lithium salt described in step S4 is LiClO4; The mass ratio of the lithium salt described in step S4 to the copper coordinated cationic cellulose nanofibrils in the copper coordinated cationic cellulose nanofibrils-anhydrous acetonitrile system is 1:4-8.
4. The method according to claim 3, characterized in that: The concentration of NaOH in the NaOH / urea aqueous solution in step S1 is 7% by mass, and the concentration of urea is 12% by mass; The concentration of the glycidyl trimethyl ammonium chloride aqueous solution in step S1 is 20% by mass; The mass ratio of the cellulose nanofibrils to glycidyl trimethylammonium chloride in step S1 is 1:4; The mass ratio of the lithium salt described in step S4 to the copper coordinated cationic cellulose nanofibrils in the copper coordinated cationic cellulose nanofibrils-anhydrous acetonitrile system is 1:
6.
5. The method according to claim 2, characterized in that: The concentration of the NaOH solution in step S2 is 8-12% by mass; The amount of NaOH solution used in step S2 is calculated based on 30-50 mL of NaOH solution per gram of copper wire; The soaking time in step S2 is 3 to 7 days.
6. The method according to claim 2, characterized in that: The stirring and mixing time in step S1 is 5 to 15 minutes; The freezing time in step S1 is 3 to 5 hours; In step S1, the reaction time under stirring is 1 to 3 hours; The washing in step S1 is performed using deionized water; The water washing in step S2 is washing with deionized water for more than 3 times until no alkali solution remains; The centrifugal conditions described in step S3 are: centrifugation at 10000 rpm for 5 to 8 minutes; The drying conditions described in step S4 are: vacuum drying at 50-60° C. for 24 h.
7. A copper-coordinated cationic cellulose nanofibril solid electrolyte, characterized in that: It is prepared by the method according to any one of claims 1 to 6.
8. Use of the copper coordinated cationic cellulose nanofibril solid electrolyte according to claim 7 in the preparation of energy storage materials.
9. Use of the copper coordinated cationic cellulose nanofibril solid electrolyte according to claim 7 in the preparation of lithium metal solid-state batteries.
10. Use of the copper coordinated cationic cellulose nanofibril solid electrolyte according to claim 7 in electric vehicles, energy storage devices, and / or portable devices.
Citation Information
Patent Citations
Cellulose nanofibril / metal-organic framework composite lithium ion battery separator and preparation method
CN108428841A
Modified cellulose nanofiber-based polymer electrolyte for all-solid-state lithium-sulfur battery and preparation method of modified cellulose nanofiber-based polymer electrolyte
CN117594872A
Electrical accumulation device
JP2007173447A
Ion-conducting structures, devices including ion-conducting structures, and methods for use and fabrication thereof
US20210202978A1